International regulation of wildlife trade: relevant legislation and organisations - Cooper, M E; Rosser, A M (Revue scientifique et technique (International Office of Epizootics), 2002)
Trade in wildlife brings into play a variety of legislation from several distinct areas of law. Many species of wildlife are subject to restrictions on international movement with the aim of protecting wild populations from over-exploitation. Animal health legislation is strictly applied to the movement of most animals to prevent the spread of infectious diseases between importing and exporting counties. The welfare of animals in the course of trade requires consideration and relevant legislation has been put into place, particularly in respect of transportation. A number of institutions have an impact on the trade itself or on the legislation that regulates wildlife trade on an international basis.